2019
DOI: 10.1155/2019/6862134
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Load Characteristics of Nonideal Explosives in a Simulation Cabin

Abstract: In this study, an aluminum-containing charge was exploded in an enclosed simulation cabin to explore the characteristics of two types of damaging pressure loads formed by internal explosions: the first incident shock wave and the quasistatic pressure. A high-frequency piezoelectric sensor was used to measure the first incident shock wave and a low-frequency piezoresistive sensor was used to measure the quasistatic pressure. After obtaining effective experimental data, the experimental results were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…e pressure-sensitive surface of the sensor and the inside of the bulkhead were maintained parallel to each other. e nylon tooling and the bulkhead interference were installed together compactly through interference fit [18]. e high-frequency piezoelectric sensor and nylon tooling for experimental use are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…e pressure-sensitive surface of the sensor and the inside of the bulkhead were maintained parallel to each other. e nylon tooling and the bulkhead interference were installed together compactly through interference fit [18]. e high-frequency piezoelectric sensor and nylon tooling for experimental use are shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Shock wave pressure is one of the important performance indicators for evaluating the damage capability of weapons and ammunition (Hong et al , 2020). Piezoelectric pressure sensors are widely used in shock wave pressure measurement because of their good dynamic characteristics and environmental adaptability (Wang et al , 2019; Feng and Ma, 2020; You and Ding, 2021). However, in a large number of explosion pressure tests, it was found that the missing consideration of the temperature influence on the piezoelectric pressure sensors was one of the main reasons for deviating results and a high variation (Krause et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ese research results have made possible the prediction and evaluation of internal explosion pressure load. In terms of mechanisms, studies on reflected shock waves mainly included theoretical calculations of multiple reflection shock waves [14][15][16], local interaction between shock wave and confined space [17][18][19][20], research on quasistatic pressure, mainly the calculation of quasistatic pressure load parameters [21][22][23], effects of postexplosive combustion on quasistatic pressure [24][25][26][27], effects of shape and structure of pressure relief hole on quasistatic pressure [28][29][30][31][32], and internal explosion load characteristics of nonideal explosives [33][34][35]. In contrast to research on single chambers, today's research on the internal explosion pressure load of multichamber structures is inadequate.…”
Section: Introductionmentioning
confidence: 99%